PERKEMBANGAN GARAP MUSIK KESENIAN REOG KENDANG SANGGAR SENI PRANA KESUMA AJI DI KABUPATEN TULUNGAGUNG - Wahyu Ardianto; Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2024)
This research aims to analyze the development of music production and the factors driving development in the Reog Kendang Performing Art Prana Kesuma Aji Art Studio in Tulungagung Regency (2017-2021). This problem was analyzed using theories put forward by several figures. In the process of analyzing the development of music production, Reog Kendang Performing Art uses theories from Edy Sedyawati, Rahayu Supanggah, and Kuntowijoyo, and to explain the driving factors using Koentjoroningrat theory. This research uses qualitative methods, with stages of data collection, data analysis, and data presentation. Data collection stages include interviews, observation, documentation and transcription. Data analysis stages include data reduction, data presentation, and drawing conclusions. The data presentation stages are obtained from the results of data collection and data analysis and then presented in a scientific work. The development that occurred was the addition and change of garap elements in the Reog Kendang Performing Art of the Prana Kesuma Aji Art Studio, including garap materials, garap materials, garap facilities, garap furniture or tools, garap determinants, and garap considerations. Development occurs due to the influence of driving factors including individual awareness, quality of expertise, and stimulating systems.